Analisis Pendekatan Historis terhadap Diksi Istilah-istilah Perekonomian dalam Al-Qur’an - Bustomi Bustomi (IAIN Bengkulu, 2020)
Al-Qur'an is a holy book with very valuabel Arabic language. Its language style is a miracle that no human can imitate until the end of time. The content of the meaning is very broad and the lexical choices are super precise and thorough. The Qur'an came down in Mecca and Medina where the majority of the population work as traders. Hence, this article is aimed at analyzing historically the lexical choices used in the Al-Qur'an whose people are generally busy in commerce. This study uses a qualitative approach by adopting the content analysis method of Satori and Komariah (2010); an analysis focusing on the actual content in a script to determine certain words, themes, concepts, phrases, or sentences related to the objectives will be achieved. In this case, the object analyzed is certain vocabulary in the Qur'an which has economic nuances. The result of this study explains that the Qur'an uses many economic terms and vocabularies which are usually used by the Arab community as a merchant community. The use of economic vocabulary such as tijârah, mȋzan, ajr, isytarâ and it’s derivatives, and jazâ is not only used to regulate proper business procedures in worldly affairs, but is actually used to guide people to do good deeds in the hereafter interest.